The ST2+ Treg/amphiregulin axis protects from immune-mediated hepatitis - Wachtendorf, Selina; Jonin, Fitriasari; Ochel, Aaron; Heinrich, Fabian; Westendorf, Astrid M.; Tiegs, Gisa; Neumann, Katrin (Frontiers in Immunology, 2024)
The alarmin IL-33 has been implicated in the pathology of immune-mediated liver diseases. IL-33 activates regulatory T cells (Tregs) and type 2 innate lymphoid cells (ILC2s) expressing the IL-33 receptor ST2. We have previously shown that endogenous IL-33/ST2 signaling activates ILC2s that aggravate liver injury in murine immune-mediated hepatitis. However, treatment of mice with exogenous IL-33 before induction of hepatitis ameliorated disease severity. Since IL-33 induces expression of amphiregulin (AREG) crucial for Treg function, we investigated the immunoregulatory role of the ST2 + Treg/AREG axis in immune-mediated hepatitis. We identified IL-33-responsive ST2 + Tregs as an effector Treg subset in the murine liver, which was highly activated in immune-mediated hepatitis. Lack of endogenous IL-33 signaling in ST2-deficient mice aggravated disease pathology. This was associated with reduced Treg activation. Adoptive transfer of exogenous IL-33-activated ST2 + Tregs before induction of hepatitis suppressed inflammatory T-cell responses and ameliorated disease pathology. We further showed increased expression of AREG by hepatic ST2 + Tregs and ILC2s in immunemediated hepatitis. Areg -/-mice developed more severe liver injury, which was associated with enhanced ILC2 activation and less ST2 + Tregs in the inflamed liver. Exogenous AREG suppressed ILC2 cytokine expression and enhanced ST2 + Treg activation in vitro. In addition, Tregs from Areg -/-mice were impaired in their capacity to suppress CD4 + T-cell activation in vitro. Moreover, application of exogenous IL-33 before disease induction did not protect Foxp3 Cre+ x ST2 fl/fl mice lacking ST2 + Tregs from immune-mediated hepatitis. In summary, we describe an immunoregulatory role of the ST2 + Treg/AREG axis in immune-mediated hepatitis, in which AREG suppresses the activation of hepatic ILC2s while maintaining ST2 + Tregs and reinforcing their immunosuppressive capacity in liver inflammation.